2014
DOI: 10.3892/ijo.2014.2484
|View full text |Cite
|
Sign up to set email alerts
|

Differentially expressed proteins in human breast cancer cells sensitive and resistant to paclitaxel

Abstract: The resistance of cancer cells to chemotherapeutic drugs represents a major problem in cancer treatment. Despite all efforts, mechanisms of resistance have not yet been elucidated. To reveal proteins that could be involved in resistance to taxanes, we compared protein expression in whole cell lysates of SK-BR-3 breast cancer cells sensitive to paclitaxel and in lysates of the same line with acquired resistance to paclitaxel. The resistant SK-BR-3 cell line was established in our lab. Protein separation was ach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 70 publications
0
7
0
Order By: Relevance
“…To verify the causal link between ABCB1 overexpression and the origin of PDT resistance derived from KP1 and KP6 porphyrins, we investigated cells with acquired MDR resistance to paclitaxel strongly overexpressing ABCB12223. Paclitaxel-resistant cells MCF-7/PacR were loaded with PS and their fluorescence and phototoxicity after light exposure was evaluated and compared to parental paclitaxel-sensitive MCF-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…To verify the causal link between ABCB1 overexpression and the origin of PDT resistance derived from KP1 and KP6 porphyrins, we investigated cells with acquired MDR resistance to paclitaxel strongly overexpressing ABCB12223. Paclitaxel-resistant cells MCF-7/PacR were loaded with PS and their fluorescence and phototoxicity after light exposure was evaluated and compared to parental paclitaxel-sensitive MCF-7 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Both resistant sublines overexpress multi-drug resistance transporters ABCB1 and ABCC3 (Němcová-Furstová et al, 2016). Moreover, both sublines also express other proteins which may be involved in resistance to paclitaxel (Pavlíková et al, 2014, Pavlíková et al, 2015). Our previous results have showed that novel taxanes with modified structures, especially at the C′3 and C3′N positions (Jelínek et al, 2013, Kovář et al, 2009, Vobořilová et al, 2011), were able to overcome paclitaxel resistance and induced cell death in tested paclitaxel-resistant breast cancer sublines (Němcová-Furstová et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…2DE was performed as described previously . Briefly, an IPGphor focusing unit (GE Healthcare, Uppsala, Sweden) was used for isoelectric focusing of samples loaded on 7 cm long, pH 3–11 Immobiline DryStrips (GE Healthcare, Uppsala, Sweden).…”
Section: Methodsmentioning
confidence: 99%